Interreligious Relations in the Structural Da'wah Framework - Arifin Zain; Maturidi Maturidi (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
This paper examines the Medina Charter, the 1945 Constitution, and Aceh Qanun No. 4 of 2016 as a fundamental source of structural da'wah policies. Structural da'wah is a character of da'wah that involves the state directly in regulating policies related to the implementation of da'wah. The primary purpose of this research is to describe the role and position of the Medina Charter, the 1945 Indonesian Constitution, and Aceh Qanun No. 4 of 2016, being the basis for the implementation of structural da'wah and discussed the regulation about the inter-religious correlation in those three regulations. This research is qualitative research using the content analysis method. The results showed that the Medina Charter, the 1945 Indonesian Constitution, and Aceh Qanun No. 4 of 2016 is a state acknowledgment of the structural da'wah implementation in Aceh because the da'wah is under the direct control of the state or government. The Medina Charter, as a result of the Prophet's ijtihad, contains guidelines for inter-religious relations and the role of the state in regulating people's lives. The 1945 Constitution of Indonesia is the highest source of law in the Republic of Indonesia, which states the guarantees the independence of citizens to embrace religion according to their beliefs. While Aceh Qanun No. 4 contains the rules for spreading religion amid society.